2016
DOI: 10.1177/1535370216636725
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Stable expression of miR-34a mediates fetal hemoglobin induction in K562 cells

Abstract: Sickle cell anemia is a common genetic disorder caused by a point mutation in the sixth codon of the b-globin gene affecting people of African descent worldwide. A wide variety of clinical phenotypes ranging from mild to severe symptoms and complications occur due to hemoglobin S polymerization, red blood cell sickling, and vaso-occlusion. Research efforts are ongoing to develop strategies of fetal hemoglobin (HbF; a 2 g 2 ) induction to inhibit sickle hemoglobin polymerization and improve clinical outcomes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…In a subset of patients with SCD treated with HC, expression of MIR26B and MIR151‐3P was associated with HbF levels at a maximum tolerated dose (Walker et al , ). Previous studies by our group demonstrated that MIR34A mediated HbF induction in K562 cells by repression of STAT3 expression, a known repressor of HBG (Ward et al , ). Previously, Lee et al () confirmed overexpression of LIN28B decreased MIRLET7 miRNA family expression and increased HbF levels in primary erythroid cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a subset of patients with SCD treated with HC, expression of MIR26B and MIR151‐3P was associated with HbF levels at a maximum tolerated dose (Walker et al , ). Previous studies by our group demonstrated that MIR34A mediated HbF induction in K562 cells by repression of STAT3 expression, a known repressor of HBG (Ward et al , ). Previously, Lee et al () confirmed overexpression of LIN28B decreased MIRLET7 miRNA family expression and increased HbF levels in primary erythroid cells.…”
Section: Discussionmentioning
confidence: 87%
“…An attractive class of molecules under development for therapeutic intervention are microRNA (miRNA) mimics and antagomirs. Due to their capacity to restore control of aberrantly expressed genes, causing a wide array of human diseases, the development of miRNA therapeutics is highly investigated (Bianchi et al , ; Walker et al , ; Ward et al , ; Lulli et al , ; Starlard‐Davenport et al , ). In previously published work, we demonstrated that MIR29B , inhibits de novo synthesis of the DNMT enzymes DNMT3A and DNMT3B, in breast cancer cells and restores control of aberrantly expressed tumour suppressor genes involved in cell cycle control, including TP73, CDH1, RASSF1, CCNA1 , and CDKN1C (Starlard‐Davenport et al , ).…”
mentioning
confidence: 99%
“…They target mRNAs in a sequence specific fashion and prompt translational repression or decay of the target mRNA . Usually, microRNA targets the 3′‐UTR of their target mRNA, but it is also possible that microRNA can bind the 5′‐UTR and gene promoter regions …”
Section: Introductionmentioning
confidence: 99%
“…Additional work by Miller et al [20] verified the ability of LIN28B to repress let-7 miRNA expression as a mechanism of HbF induction in tissue culture systems. Recently, we published data to support a role of miR34a in γ -globin activation [21] through STAT3 gene silencing. Our group previously demonstrated a negative role of STAT3 in γ -globin expression [22].…”
mentioning
confidence: 99%